2016
DOI: 10.1007/s00134-016-4398-0
|View full text |Cite
|
Sign up to set email alerts
|

Focus on veno-venous ECMO in adults with severe ARDS

Abstract: Veno-venous extracorporeal membrane oxygenation (vvECMO) improves oxygenation and promotes carbon dioxide (CO 2 ) removal [1,2]. In the most severe form of ARDS, ECMO rapidly facilitates the correction of severe derangement in gas exchange and saves time, which allows one to treat the cause of lung injury. Recent advances in ECMO technology have improved safety and promoted its use [3][4][5].Knowledge of the gas exchange performance of membrane oxygenators is important to help choose the optimal system for pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Extracorporeal circulation (ECC), initially developed to allow few hours long cardiac surgery interventions, 1 has been used for decades as a respiratory and/or circulatory support in case of severe acute respiratory distress syndrome (ARDS), 2,3 cardiogenic shock, or refractory cardiac arrest 4 over periods of several days to several weeks, thanks to Extra Corporeal Membrane Oxygenation (ECMO) support. The ECMO circuitry requires an anticoagulation therapy that must be closely and frequently monitored due to a high risk of hemorrhagic and thrombotic complications.…”
Section: Introductionmentioning
confidence: 99%
“…Extracorporeal circulation (ECC), initially developed to allow few hours long cardiac surgery interventions, 1 has been used for decades as a respiratory and/or circulatory support in case of severe acute respiratory distress syndrome (ARDS), 2,3 cardiogenic shock, or refractory cardiac arrest 4 over periods of several days to several weeks, thanks to Extra Corporeal Membrane Oxygenation (ECMO) support. The ECMO circuitry requires an anticoagulation therapy that must be closely and frequently monitored due to a high risk of hemorrhagic and thrombotic complications.…”
Section: Introductionmentioning
confidence: 99%
“…A dramatic expansion of ECMO use over the last decade has led to the increased number of respiratory ECMO centers as well (9). Experts argue that such an uncontrolled increase in ECMO use will inevitably compromise the outcomes of patients treated with ECMO due to inexperience with the method, thus leading to the erroneous conclusion that the method itself is ineffective (10). Unfortunately, such suboptimal performance due to inexperience has been reported (11).…”
Section: Discussionmentioning
confidence: 99%
“…This last segment is the application of ECMO principally, and this level of mortality is usually what we want reduce by ECMO support. 109 But despite the efforts and promising results, this reduction of mortality is not consistently reached, and the application of ECMO in COVID-19 has demonstrated that the main goal is to apply the support to patients that have a real chance of survival and to apply the support at the right time. 32,49,50 One possible approach is personalized medicine to underline the biological processes common among different subpopulations in the same wide-ranging clinical category or definition.…”
Section: Ecmo and Indications: The Intersection Of Enthusiasm And Pat...mentioning
confidence: 99%